A Scoping Review of Non-invasive Imaging Modalities in Dermatological Disease: Potential Novel Biomarkers in Hidradenitis Suppurativa - Grand, David; Navrazhina, Kristina; Frew, John W. (Frontiers in Medicine, 2019)
Background: The development of imaging-based biomarkers has the potential to overcome major challenges in the accurate and reproducible assessment of disease severity and response to novel therapies in Hidradenitis Suppurativa (HS). Understanding the advantages and limitations of existing non-invasive imaging modalities in dermatological disease will aid in the development of hypotheses and inform the design of future studies. Methods: A scoping review was performed using Medline, Embase, Web of Science Databases and evaluation of ‘grey literature’ until June 30, 2019. Citations were examined according to pre-defined inclusion and exclusion criteria. Citations were reviewed by two independent reviewers. Narrative Synthesis was used to summarize data, structured by imaging modality. Results: Non-invasive imaging modalities, such as ultrasound, MRI, RCM, EIS, OCT and MIT, were identified. Only ultrasound, MRI and MIT have been used in HS. Image modalities vary in image depth, resolution, cost, accessibility and correlation with known aspects of disease activity in HS. Discussion and Conclusion: The benefits and limitations of each imaging modality are products of cost, accessibility, validity and reliability. An additional hurdle to the development of image-based biomarkers in HS is a lack of established analytical benchmarks that can be correlated with existing biological, inflammatory and clinical parameters. This review has identified potential imaging biomarkers, as well as relevant analytical benchmarks that reflect the presence or absence of disease. Further investigation work is needed to analytically and clinically validate these imaging variables in order to identify potential imaging biomarkers in HS.